Phonetic detail is used to predict a word's morphological composition. (July 2021) - Clayards, Meghan; Gaskell, M. Gareth; Hawkins, Sarah
Highlights: Phonemically-identical English true and pseudo prefixes differ in phonetic detail. Eye movements show listeners use this detail in real time to predict word identity. Effects reduced during the task as participants learned about cue availability. Rhythmic properties of true prefixes may help listeners identify them as morphemes. Abstract: An eye-tracking experiment tested the hypothesis that listeners use within-word fine phonetic detail that systematically reflects morphological structure, when the phonemes are identical ( dis in discolour (true prefix) vs. discover (pseudo prefix)) and when they differ ( re-cover vs. recover ). Spoken sentence pairs, identical up to at least the critical word (e.g. I'd be surprised if the boys discolour/discover it ), were cross-spliced at the prefix-stem boundary to produce stimuli in which the critical syllable's acoustics either matched or mismatched the sentence continuation. On each trial listeners heard one sentence, and selected one of two photographs depicting the pair. Matched and mismatched stimuli were heard in separate sessions, at least a week apart. Matched stimuli led to more looks to the target photograph overall and time-course analysis suggested this was true at the earliest moments. We also observed stronger effects for earlier trials and the effects tended to weaken over the course of the experiment. These results suggest that normal speech perception involves continuously monitoring phonetic detail, and, when it is systematically associated with meaning, using it to facilitate rapid understanding.